2009
DOI: 10.1590/s0100-879x2009000500004
|View full text |Cite
|
Sign up to set email alerts
|

Association of HDL cholesterol and triglycerides with mortality in patients with heart failure

Abstract: It has been demonstrated that there is an association between serum lipoproteins and survival rate in patients with ischemic cardiomyopathy, as well as in patients with non-ischemic causes of heart failure. We tested the hypothesis of an association between serum lipoprotein levels and prognosis in a cohort of outpatients with heart failure, including Chagas' heart disease. The lipid profile of 833 outpatients with heart failure in functional classes III and IV of the New York Heart Association, with a mean ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
2
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 23 publications
1
20
2
4
Order By: Relevance
“…The observations of the present study indicated that the dilated cardiomyopathy patients had significantly lower HDL-C level and markedly higher TG concentrations than healthy subjects and the results are consistent with the reports of Cooke et al who demonstrated that the mean serum HDL cholesterol serum levels of congestive heart failure (CHF) patients were significantly lower than that of normal subjects (0.86 ± 0.24 and 1.2 ± 0.31 mmol/L, respectively). The present study is in contrast with the results of Freitas et al [9] who reported a higher serum HDL cholesterol levels in heart failure patients.…”
Section: Discussioncontrasting
confidence: 99%
“…The observations of the present study indicated that the dilated cardiomyopathy patients had significantly lower HDL-C level and markedly higher TG concentrations than healthy subjects and the results are consistent with the reports of Cooke et al who demonstrated that the mean serum HDL cholesterol serum levels of congestive heart failure (CHF) patients were significantly lower than that of normal subjects (0.86 ± 0.24 and 1.2 ± 0.31 mmol/L, respectively). The present study is in contrast with the results of Freitas et al [9] who reported a higher serum HDL cholesterol levels in heart failure patients.…”
Section: Discussioncontrasting
confidence: 99%
“…Low HDL‐C was also associated with a higher incidence of mortality and major adverse cardiac events in patients with acute coronary syndrome. Consistently, HDL‐C levels were found to be inversely associated with mortality in patients with heart failure . It has been reported that high‐density lipoprotein (HDL) has the property of shorting cardiac repolarization, which may contribute to reduction of sudden cardiac death .…”
Section: Introductionmentioning
confidence: 78%
“…Consistently, HDL-C levels were found to be inversely associated with mortality in patients with heart failure. 4,5 It has been reported that high-density lipoprotein (HDL) has the property of shorting cardiac repolarization, which may contribute to reduction of sudden cardiac death. 6 HDL has several well-documented functions, with the potential to protect against atherosclerosis, such as reverse cholesterol transport, anti-inflammatory and antioxidant properties, and improvement of endothelial function.…”
Section: Introductionmentioning
confidence: 99%
“…Rauchhaus and colleagues were among the first to demonstrate this paradox in a derivative/validation study in 417 patients with chronic heart failure whereby lower serum total cholesterol was independently associated with worse prognosis 24. A more recent study demonstrated that higher serum high-density lipoprotein (HDL) cholesterol and higher serum triglycerides were associated with lower mortality in a cohort of 833 outpatients with chronic heart failure due to various aetiologies 25. In contrast with the results of these studies, Christ and colleagues found that, in patients with idiopathic dilated cardiomyopathy, low cholesterol levels are dependent on the severity of cardiac disease and do not independently predict adverse outcomes in these patients 26…”
Section: Discussionmentioning
confidence: 99%